Comparative Study of the Process of Islamic Law Legislation in Indonesia with Malaysia and Its Implementation into Legislation Regulations - Ahmad Nurozi (Jurnal Hukum Islam, 2022)
Islamic law in Indonesia and Malaysia in terms of rules and regulations, to explain the position of customary law, and Islamic law in the statutory system in Indonesia and Malaysia, and to find out how the implementation of Islamic law in Indonesia and Malaysia which is a product of legislation. The results showed that the legislative process of Islamic law in Indonesia and Malaysia is colored by various methods so that it is formed into statutory provisions; Islamic legal legislation in Indonesia is the basis for the formation of laws is a reflection of regulations that become the ideology of the state philosophy not only of Islam but also for adherents of other religions. The Islamic law legislation in Malaysia begins with issues requiring legal certainty to ensure that Muslims can overcome the mistakes and problems faced. There are times when fatwas are merely fatwas and not one law. When the fatwa becomes law, if it is approved by the Sultan and agreed upon by the Majlis Mesyuarat of their respective Kingdoms if the regulation is in line with the basis of the determination, then the law can be applied; on the contrary, the established law is not in line with the vision and mission of the nation, then the product of the legislation will disappear control.